Liam Anderson y Gareth Stansfield, Crisis in Kirkuk: the Ethnopolitics of Conflict and Compromise, Filadelfia, University of Pennsylvania Press, 2009, 298 pp. - Castillo Quíñones, Juan Carlos (Estudios de Asia y África, 2013)
Liam Anderson y Gareth Stansfield, Crisis in Kirkuk: the Ethnopolitics of Conflict and Compromise, Filadelfia, University of Pennsylvania Press, 2009, 298 pp.